2018
DOI: 10.5398/tasj.2018.41.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cellulolytic Lactic-Acid Bacteria from Mentok (Anas moschata) Gastro-Intestinal Tract

Abstract: Mentok, a local Indonesian name's of muscovy duck (Anas moschata), has been known as a duck with the capability to consume poor quality feed, high with non-starch carbohydrate (NSP) content. This capacity occurs because of the presence of microbial fermentation activity in the gastro intestinal tract (GIT) of mentok. However, the information about the identification and characterization of the cellulolytic microbes involved is limited. This study was expected to provide scientific contributions about gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Khan and Iqbal (2016) documented that organic acids could increase the activity of fiberdegrading enzymes resulting in increased crude fiber digestibility. Likewise, lactic acid bacteria may produce cellulolytic enzymes that can degrade the crude fiber in the feed as reported by Herdian et al (2018).…”
Section: Discussionmentioning
confidence: 96%
“…Khan and Iqbal (2016) documented that organic acids could increase the activity of fiberdegrading enzymes resulting in increased crude fiber digestibility. Likewise, lactic acid bacteria may produce cellulolytic enzymes that can degrade the crude fiber in the feed as reported by Herdian et al (2018).…”
Section: Discussionmentioning
confidence: 96%
“…reported that phenolic compounds of eight berries inhibited the growth of selected gram-negative bacteria and were not active against gram positive LAB. Increasing LAB population in broiler chicken indicated the better gastrointestinal conditions, because LAB potentially improved nutrient digestibility especially with cellulose content (Herdian et al, 2018).…”
Section: Microbial Populationsmentioning
confidence: 99%
“…Just like starch, cellulose can be exploited for LA production if it is in the presence of a LAB able to metabolize it. Saowapar et al (2014) and Herdian et al (2018) in the course of their work showed that the cellulase activity of LAB not only varied between isolates from different biotopes but also varied between isolates from the same biotope. Similar data were observed in our study and cellulase from isolate1B9 showed the most significant activity with a production of 7.98 μg of glucose per ml of solution for one minute.…”
Section: Discussionmentioning
confidence: 99%
“…Saowapar et al. (2014) and Herdian et al. (2018) in the course of their work showed that the cellulase activity of LAB not only varied between isolates from different biotopes but also varied between isolates from the same biotope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation